How to live without International Investment Agreements? Following International Investment Law to build internal law attractive to investment and that prevent Investor- State conflicts - Saco, Víctor (2018)
This article develops the following idea: A change in the internal regulatory framework related to foreign investors in a State can be useful to prevent conflicts and Investor-Sate Dispute Settlement. Also it can serve to States that have terminated its international agreements to remain attractive to Foreign Direct Investment at the legal level. The change of the internal regulation may follow the basic standards of International Investment Agreements in order to achieve this goal.